Failures of masonry and adobe buildings during the June 23, 2011 Maden-(Elazig) earthquake in Turkey - Sayin, Erkut; Yon, Burak; Calayir, Yusuf; Karaton, Muhammet (Pergamon-Elsevier Science Ltd, 2013)
This paper evaluates the failures of masonry and adobe buildings during the June 23, 2011, Maden (Elazig) earthquake. Maden is a township approximately 80 km away from Elazig city in Turkey. The magnitude of the earthquake was announced as M-L. = 5.3 by the Earthquake Division of the Turkish Disaster and Emergency Management Agency (DEMA). Most of masonry and adobe buildings in Maden and the neighboring settlements had been damaged severely at this moderate earthquake. In this paper, reasons of damages and failures of these structures which are lack of engineering services were examined and explained in detail. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Elazig-Maden earthquake; Masonry and adobe buildings; Earthquake damage